Evaluation of in vivo genotoxicity induced by N‐ethyl‐N‐nitrosourea, benzo[a]pyrene, and 4‐nitroquinoline‐1‐oxide in the Pig‐a and gpt assays. (18th September 2013) - Horibata, Katsuyoshi; Ukai, Akiko; Kimoto, Takafumi; Suzuki, Tetsuya; Kamoshita, Nagisa; Masumura, Kenichi; Nohmi, Takehiko; Honma, Masamitsu
Abstract : The recently developed Pig‐a mutation assay is based on flow cytometric enumeration of glycosylphosphatidylinositol (GPI) anchor‐deficient red blood cells caused by a forward mutation in the Pig‐a gene. Because the assay can be conducted in nontransgenic animals and the mutations accumulate with repeat dosing, we believe that the Pig‐a assay could be integrated into repeat‐dose toxicology studies and provides an alternative to transgenic rodent (TGR) mutation assays. The capacity and characteristics of the Pig‐a assay relative to TGR mutation assays, however, are unclear. Here, using transgenic gpt delta mice, we compared the in vivo genotoxicity of single oral doses of N ‐ethyl‐ N ‐nitrosourea (ENU, 40 mg/kg), benzo[ a ]pyrene (BP, 100 and 200 mg/kg), and 4‐nitroquinoline‐1‐oxide (4NQO, 50 mg/kg) in the Pig‐a (peripheral blood) and gpt (bone marrow and liver) gene mutation assays. Pig‐a assays were conducted at 2, 4, and 7 weeks after the treatment, while gpt assays were conducted on tissues collected at the 7‐week terminal sacrifice. ENU increased both Pig‐a and gpt mutant frequencies (MFs) at all sampling times, and BP increased MFs in both assays but the Pig‐a MFs peaked at 2 weeks and then decreased. Although 4NQO increased gpt MFs in the liver, only weak, nonsignificant increases (two‐ or threefold above control) were detected in the bone marrow in both the Pig‐a and the gpt assay. These findings suggest that further studies are needed to elucidate the kinetics of the Pig‐a mutation assay in order to use it as an alternative to the TGR mutation assay. Environ. Mol. Mutagen. 54:747–754, 2013. © 2013 Wiley Periodicals, Inc.